A General Strategy toward Carbon Cloth‐Based Hierarchical Films Constructed by Porous Nanosheets for Superior Photocatalytic Activity. Issue 20 (21st January 2015) - Li, Linlin; Peng, Shengjie; Wang, Na; Srinivasan, Madhavi; Mhaisalkar, Subodh G.; Yan, Qingyu; Ramakrishna, Seeram
<x xml:space="preserve">Abstract</x> Herein, the controlled synthesis of 3D hierarchical films on carbon cloth (CC) in a high yield through a hydrothermal process and their high photocatalytic properties are reported. As representative examples, the obtained ZnIn2S4/CdIn2S4 composites are composed of porous nanosheets. During the hydrothermal process, l‐cysteine plays an important dual role as a coordinating agent and sulfur source, which is in favor of adjusting stoichiometry of the final product and forming the nanoporous structure. This facile method can be extended to synthesize other sulfides and oxides on CC substrates, such as CoIn2S4, MnIn2S4, FeIn2S4, SnS2, and Bi2WO6. When evaluated the photocatalytic activity, the optimized ZnIn2S4/CdIn2S4(20%)‐CC with an easily recycling feature shows higher photocatalytic degradation activity for methylene blue (MB) than ZnIn2S4‐CC, CdIn2S4‐CC, and ZnIn2S4/CdIn2S4(20%) powder. More importantly, ZnIn2S4/CdIn2S4(20%)‐CC also exhibits superior H2 production activity. The enhanced photocatalytic activity is attributed to the unique porous sheet‐like structure and the formation of heterojunction. Our results could provide a promising way to develop high‐performance photocatalytic films, which makes it possible to be used in real devices.